Hematopoietic stem cell size heterogeneity is not linked to changes in stem cell potential of aged HSCs - Saçma, Mehmet; Hageb, Ali; Zadro, Alex; Schuster, Tanja; Vogel, Mona; Eiwen, Karina; Sakk, Vadim; Geiger, Hartmut (Frontiers in Aging, 2025)
Aging is associated with a decline in the function of hematopoietic stem cells (HSCs). This decline in HSC function results in reduced hematologic regenerative capacity and an increased incidence of hematologic disorders. In general, aged HSCs show on average an increase in cell size and a lower frequency of cells polar for protein polarity markers. The size of an HSCs has been proposed to be tightly linked to the potential of the HSCs, with small HSCs showing a higher potential compared to large HSCs. The increase in size of HSCs upon aging may be associated with the reduced potential of aged HSCs. HSCs are located within the bone marrow (BM) in distinct microenvironments called niches. These niches provide critical physical and molecular signals that are essential for HSC self-renewal, proliferation, migration and differentiation. There are multiple types of functional niches, and HSCs within these distinct types of niches show a distinct type of potential. Furthermore, the distribution of HSCs relative to niches changes upon aging. It is not known whether there is a correlation of HSCs size, HSCs polarity and the location of HSCs in distinct types of niches, as might be expected, as all three (size, polarity and position) have been linked to HSC potential. Here we show that in young mice smaller HSCs, which are more myeloid-biased, are preferentially located at central BM niches, including sinusoids and megakaryocytes. In contrast, larger HSCs, which show a bias toward B-lymphoid differentiation, are preferentially located in endosteal BM niches close to arterioles. However, in aged mice, which also contain HSCs of different sizes, there was no correlation between HSC size and localization and potential. Furthermore, within the hematopoietic stem and progenitor cell (HSPC) population, cell size increases as the cells become more limited in their capacity. Notably, we further report that changes in the level of polarity correlate with HSC potential even in aged mice.